What drives changes in surface water salinity in coastal Bangladesh? - Haq, Md Izazul; Shamsudduha, Mohammad; Zahid, Anwar; Ahmed, Kazi Matin; Kamal, A. S. M. Maksud; Taylor, Richard G. (Frontiers in Water, 2024)
The salinisation of freshwater resources is a priority concern in Asian mega-deltas including the Bengal Basin of Bangladesh where the livelihoods, ecosystem services and health of coastal populations are increasingly under threat. Understanding trends and variations in surface water salinity is required to inform sustainable use of freshwater supplies in the face of hydrological regimes intensified by global environmental change. We interrogate 86 time series of fortnightly records of in situ surface water salinity between 1990 and 2019. Statistical and geospatial techniques were employed to characterise spatiotemporal distributions and trends in surface water salinity and identify key drivers of change in the coastal region of Bangladesh.The observed spatiotemporal structure in surface water salinity is primarily controlled by the magnitude and seasonality of river discharge entering the delta. In the moribund delta north of the Sundarbans, the contour between fresh and brackish water migrates seasonally between ~20 and ~40 km northward during the dry season. Abrupt increases in surface water salinity are observed throughout the coastal region in response to variations in upstream river discharge; the prominence of these events highlights their importance in driving salinity increases. Areas which are better connected to more voluminous seasonal river discharge (active delta), show greater recovery to these episodic inundations by cyclones than those less-well flushed by river discharge (moribund delta). Our reported observations provide a baseline for understanding the consequences of global environmental change and informing more climate-resilient adaptation strategies in coastal environments of Bangladesh and other Asian Mega-deltas.